Facts About Fluoride - Anne Kendall (EDIS)
FCS8798, a 2-page fact sheet by Anne Kendall, discusses the reasons we need fluoride, how to get enough fluoride, and consequences of excess fluoride. Published by the UF Department of Family, Youth and Community Sciences, July 2006.